2019
DOI: 10.1111/apa.14933
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of age, gender, height and body mass index on children's balance

Abstract: Aim This research aimed to understand the influence of age, gender, height and body mass index (BMI) on balance ability in children aged 4‐12 years. The secondary aim was to develop normative values for three balance tests on the Balance Master system. Methods Children were recruited in 2017 through community advertising. Balance testing occurred at three recreational centres in Frankston, Victoria, Australia. Data were collected by the Rhythmic Weight Shift, modified Clinical Test of Sensory Integration and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
6
12
1
Order By: Relevance
“…However, other authors, such as Nolan [ 16 ], found that girls might be superior to boys at developing postural control, with girls progressing to an ‘adult-like’ integrated open- and closed-loop strategy of controlling balance earlier than boys. These results were supported by Riach and Starkes [ 17 ], Kirshenbaum et al [ 18 ], and Kolic et al [ 19 ]. Nolan [ 16 ] also observed that greater balance ability and postural control were associated with Body Mass Index (BMI), with older female children and children with lower BMI being more likely to exhibit greater balance ability and postural control.…”
Section: Introductionsupporting
confidence: 70%
“…However, other authors, such as Nolan [ 16 ], found that girls might be superior to boys at developing postural control, with girls progressing to an ‘adult-like’ integrated open- and closed-loop strategy of controlling balance earlier than boys. These results were supported by Riach and Starkes [ 17 ], Kirshenbaum et al [ 18 ], and Kolic et al [ 19 ]. Nolan [ 16 ] also observed that greater balance ability and postural control were associated with Body Mass Index (BMI), with older female children and children with lower BMI being more likely to exhibit greater balance ability and postural control.…”
Section: Introductionsupporting
confidence: 70%
“…The most intriguing result of this study, then, was the finding of a strong relationship between high BMI and body balance. It turned out that overweight and obese children have better stability parameters than children with normal body weight, which is confirmed by many studies [ 51 , 52 ] but there are also studies that do not agree with our results [ 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussioncontrasting
confidence: 47%
“…In addition, we should note that %SMM r and BMI combined, predicted 14% of the variance observed for OLST. The negative relation between BMI and OLST observation corresponds with a previous association of higher BMI with lower postural control and balance ability [ 36 ]. Thus, BMI may act as confounding factor affecting the physiological parameters of the balance and control in addition to reducing %SMM r (as increment in BMI increases the body mass in denominator while calculating %SMM r ).…”
Section: Discussionsupporting
confidence: 81%